Acetate, a Short-Chain Fatty Acid, Acutely Lowers Heart Rate and Cardiac Contractility Along with Blood Pressure - Poll, Brian G.; Xu, Jiaojiao; Jun, Seungho; Sanchez, Jason; Zaidman, Nathan A.; He, Xiaojun; Lester, Laeben; Berkowitz, Dan E.; Paolocci, Nazareno; Gao, Wei Dong; Pluznick, Jennifer L. (The Journal of pharmacology and experimental therapeutics, 2021)
Short-chain fatty acids (SCFAs) are metabolites produced almost exclusively by the gut microbiota and are an essential mechanism by which gut microbes influence host physiology. Given that SCFAs induce vasodilation, we hypothesized that they might have additional cardiovascular effects. In this study, novel mechanisms of SCFA action were uncovered by examining the acute effects of SCFAs on cardiovascular physiology in vivo and ex vivo. Acute delivery of SCFAs in conscious radiotelemetry-implanted mice results in a simultaneous decrease in both mean arterial pressure and heart rate (HR). Inhibition of sympathetic tone by the selective β-1 adrenergic receptor antagonist atenolol blocks the acute drop in HR seen with acetate administration, yet the decrease in mean arterial pressure persists. Treatment with tyramine, an indirect sympathomimetic, also blocks the acetate-induced acute drop in HR. Langendorff preparations show that acetate lowers HR only after long-term exposure and at a smaller magnitude than seen in vivo. Pressure-volume loops after acetate injection show a decrease in load-independent measures of cardiac contractility. Isolated trabecular muscle preparations also show a reduction in force generation upon SCFA treatment, though only at supraphysiological concentrations. These experiments demonstrate a direct cardiac component of the SCFA cardiovascular response. These data show that acetate affects blood pressure and cardiac function through parallel mechanisms and establish a role for SCFAs in modulating sympathetic tone and cardiac contractility, further advancing our understanding of the role of SCFAs in blood pressure regulation. Acetate, a short-chain fatty acid, acutely lowers heart rate (HR) as well as mean arterial pressure in vivo in radiotelemetry-implanted mice. Acetate is acting in a sympatholytic manner on HR and exerts negative inotropic effects in vivo. This work has implications for potential short-chain fatty acid therapeutics as well as gut dysbiosis-related disease states.